The composition of peripheral immunocompetent cell subpopulations and cytokine content in the brain structures of mutant Disc1-Q31L mice - M. M. Gevorgyan; S. Ya. Zhanaeva; E. L. Alperina; T. V. Lipina; G. V. Idova (Вавиловский журнал генетики и селекции)
The DISC1 (disrupted in sсhizophrenia 1) gene is associated with brain dysfunctions, which are involved in a variety of mental disorders, such as schizophrenia, depression and bipolar disorder. This is the first study to examine the immune parameters in Disc1-Q31L mice with a point mutation in the second exon of the DISC1 gene compared to mice of the C57BL/6NCrl strain (WT, wild type). A flow cytometry assay has shown that intact Disc1-Q31L mice differ from the WT strain by an increase in the percentage of CD3+ T cells, CD3+CD4+ Т helper cells and CD3+CD4+CD25+ T regulatory cells and a decrease in CD3+CD8+ T cytotoxic/suppressor cells in the peripheral blood. A multiplex analysis revealed differences in the content of cytokines in the brain structures of Disc1-Q31L mice compared to WT mice. The content of pro-inflammatory cytokines was increased in the frontal cortex (IL-6, IL- 17 and IFNγ) and striatum (IFNγ), and decreased in the hippocampus and hypothalamus. At the same time, the levels of IL-1β were decreased in all structures being examined. In addition, the content of anti-inflammatory cytokines IL-4 was increased in the frontal cortex, while IL-10 amount was decreased in the hippocampus. Immune response to sheep red blood cells analyzed by the number of antibody-forming cells in the spleen was higher in Disc1-Q31L mice at the peak of the reaction than in WT mice. Thus, Disc1-Q31L mice are characterized by changes in the pattern of cytokines in the brain structures, an amplification of the peripheral T-cell link with an increase in the content of the subpopulations of CD3+CD4+ T helpers and CD3+CD4+CD25+ T regulatory cells, as well as elevated immune reactivity to antigen in the spleen.